2014
DOI: 10.1038/npp.2014.139
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Alcohol-Heightened Aggression by CRF-R1 Antagonists in Mice: Critical Role for DRN-PFC Serotonin Pathway

Abstract: Alcohol can escalate aggressive behavior in a significant subgroup of rodents, humans, and nonhuman primates. The present study investigated whether blockade of corticotropin-releasing factor receptor type 1 (CRF-R1) could prevent the emergence of alcoholheightened aggression in mice. The serotonin (5-HT) pathway from the dorsal raphe nucleus (DRN) to the medial prefrontal cortex (mPFC) by CRF-R1 was investigated as a possible target for the prevention of alcohol-heightened aggressive behavior. Male CFW mice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 63 publications
(96 reference statements)
1
15
0
Order By: Relevance
“…Our results confirm that the mPFC plays a large role in the transition to EtOH dependence (George et al 2013; Kroener et al 2012; Holmes et al 2012), withdrawal from drugs of abuse (Williams and Steketee 2004) and EtOH-related aggression (Quadros et al 2014). The mPFC has long been associated with the inhibitory control of emotional outbursts, including aggression and violence (Nelson and Trainor 2007; Siegel et al 1974).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results confirm that the mPFC plays a large role in the transition to EtOH dependence (George et al 2013; Kroener et al 2012; Holmes et al 2012), withdrawal from drugs of abuse (Williams and Steketee 2004) and EtOH-related aggression (Quadros et al 2014). The mPFC has long been associated with the inhibitory control of emotional outbursts, including aggression and violence (Nelson and Trainor 2007; Siegel et al 1974).…”
Section: Discussionsupporting
confidence: 88%
“…Our laboratory has been using CFW mice for almost four decades to study the pharmacology of aggressive behavior (Miczek and O’Donnell 1978; Quadros et al 2014). These mice are the most commonly studied among outbred stocks (Festing 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Memantine, neramexane, and mGluR5 antagonist MTEP interacted with alcohol to further increase alcohol-heightened aggression in mice, whereas mGluR2/3 agonist LY379268 did not 81 . CRF type-1 receptors regulate serotonin function from the dorsal raphe nuclei (DRN)- mPFC to alter alcohol-heightened aggression 82 , so glutamate may influence the mPFC for the expression of low-dose alcohol-related behavior.…”
Section: Low-level Drinkingmentioning
confidence: 99%
“…Further pharmacological studies of alcohol-escalated aggressive behavior revealed that antagonists of serotonin 1A and 1B receptors, GABA A receptors, glutamate and corticotrophin releasing factor receptor subtypes can exert behaviorally selective anti-aggressive effects in mice, rats, and monkeys [2029]. Considerably less is known about the neurobiology of escalated aggressive behavior that emerges during withdrawal from prolonged exposure to alcohol.…”
Section: Animal Models Of Maladaptive Pathological Aggressionmentioning
confidence: 99%